Has computational creativity successfully made it “Beyond the Fence” in musical theatre? - Anna Jordanous (Connection Science)
A significant test for software is to task it with replicating human performance, as done recently with creative software and the commercial project Beyond the Fence (undertaken for a television documentary Computer Says Show). The remit of this project was to use computer software as much as possible to produce “the world's first computer-generated musical”. Several creative systems were used to generate this musical, which was performed in London's West End in 2016. This paper considers the challenge of evaluating this project. Current computational creativity evaluation methods are ill-suited to evaluating projects that involve creative input from multiple systems and people. Following recent inspiration within computational creativity research from interaction design, here the DECIDE evaluation framework is applied to evaluate the Beyond the Fence project. Evaluation finds that the project was reasonably successful at achieving the task of using computational generation to produce a credible musical. Lessons have been learned for future computational creativity projects though, particularly for affording creative software more agency and enabling software to interact with other creative partners. Upon reflection, the DECIDE framework emerges as a useful evaluation “checklist” (if not a tangible operational methodology) for evaluating multiple creative systems participating in a creative task.